The Role Of Brand Awareness And Customer Experience In Increasing Customer Loyalty At Nailogy Bali - Apriningsih, Dewa Ayu Putu; Ardani, Wayan; Widani, Ni Made (Pasundan Social Science Development, 2025)
Customer loyalty greatly influences the success of a business, especially businesses that must follow current trend updates such as Nailart businesses. This study aims to determine the influence of brand awareness and customer experience in increasing customer loyalty at Nailogy Bali. The population in this study were all Nailogy Bali customers totaling 45,533 in 2024. The sample size obtained was 100 customers at Nailogy Bali. The sample size was calculated using the Slovin formula. The sample used in this study was taken using a purposive sampling method. Testing was carried out by testing research instruments, Classical Assumption Tests, with data analysis techniques using Multiple Linear Regression Analysis, Determination Analysis, Partial Test (T Test) and Simultaneous Test (F Test). The findings in this study are that brand awareness has a positive and significant effect on Nailogy Bali customer loyalty with a calculated t value of 5.372 with a significance value of 0.000 (0.000 <0.05) and a regression coefficient that has a positive value of 0.331. Customer experience has a positive and significant effect on customer loyalty of Nailogy Bali with a calculated t value of 10.172 with a significance value of 0.006 (0.000 <0.05) and a regression coefficient of 0.490. Brand awareness and customer experience simultaneously have a positive and significant effect on customer loyalty of Nailogy Bali with a calculated F value of 185.716 with a significance of 0.000. Because the significance value is smaller than 0.05 (0.000 <0.05). The results of this study are expected to be a reference for Nailogy Bali management that to increase customer loyalty, it is necessary to increase brand awareness and customer experience.